Return of the Salish Sea Harbor Porpoise, Phocoena phocoena: Knowledge Gaps, Current Research, and What We Need to Do to Protect Their Future - Elliser, Cindy R.; Hall, Anna (Frontiers in Marine Science, 2021)
The harbor porpoise (Phocoena phocoena) is one of the most abundant coastal cetacean species in the Northern Hemisphere with differential levels of regional knowledge. Gaps are particularly evident for the Pacific subspecies P.p.vomerina. In the Salish Sea (a transboundary body of water spanning between Washington, United States (U.S.) and British Columbia (B.C.), Canada), there is a dearth of information on many aspects of the biology, ecology, behavior, sociality and regionally specific threats. Here we present a case study of the Salish Sea harbor porpoise, combining historical and current research, from both B.C. and Washington, to provide a more holistic view of this species’ status, the knowledge continuum and gaps, risks from identified threats and what current research and collaborations are revealing about this enigmatic species. The Salish Sea harbor porpoise was abundant to the 1940s and 1950s, but by the 1990s their numbers were greatly reduced, and all but absent in some areas. By the early 2000s, numbers had resurged, and harbor porpoise are now once again found throughout much of the Salish Sea. Despite this, studies focused on Salish Sea harbor porpoises have been limited until recently. Current long-term research has been conducted from vessels and land in both Canada and the U.S. Multi-faceted work using techniques including photo-identification (photo-ID), behavioral visual observations, acoustics, commercial fishery surveys, sighting reports, citizen science and other ecological data have provided insight into the seasonal variation in density and abundance, site fidelity, reproduction, by-catch rates, foraging and the identification of important habitats that are used intra- and inter-annually in this region. These may represent culturally and biologically significant habitats for Salish Sea harbor porpoise. Collaborations within and outside of the Salish Sea have revealed consistencies and dissimilarities between different communities or populations; indicating that some aspects are more uniform for the species, while others may be community or population specific. The importance of long-term broad and fine-scale research is highlighted, as well as recommendations to further close the knowledge gaps and reduce the known human threats within the Salish Sea.